Digital Financial Literacy and Financial Behavior of Millennials: Empirical Findings from Makassar City - Chaerunnisa Rumianti; Ansir Launtu (Lembaga Publikasi Ilmiah Nusantara, 2026)
Advances in financial technology have changed how financial services and products are accessed and delivered, significantly influencing the financial behavior of millennials. This study examines the influence of digital financial literacy on millennials' financial behavior in Makassar City, Indonesia. Using a quantitative approach, data were collected via an electronic questionnaire distributed on social media platforms such as LinkedIn and Facebook. Six hundred ten valid responses were analyzed using Structural Equation Modeling (SEM) to examine the relationships among variables. The results show that all dimensions of digital financial literacy, namely digital knowledge, digital experience, digital skills, and digital awareness, positively and significantly influence financial behavior. Digital financial literacy equips millennials with the knowledge and skills to make informed financial decisions, access online financial tools, and manage their financial resources effectively. This study contributes to the literature on digital financial literacy in developing countries and offers strategic recommendations for policymakers, educators, and financial institutions to empower millennials in the digital era.